HUBUNGAN HEMATOKRIT, TROMBOSIT, DAN STATUS NUTRISI TERHADAP MORTALITAS PASIEN DEMAM BERDARAH DENGUE : Tinjauan Pustaka Sistematis - Zafirah Ariibah Saniyyah Indrapati, (2020)
Dengue Hemorrhagic Fever (DHF) is an infection induced by DENV virus, and transmitted by Aedes Spp vector to human. DHF is the world's fastest transmitting mosquito-borne viral infectious disease with high mortality. Therefore, identifying the causes of high mortality in DHF patients is necessary. Several studies have discussed the correlation between hematocrit, thrombocyte,nutritional status and mortality of DHF patients with diversed results. The aims of this study are to provide a reference standard for establishing management of DHF and to identify mortality of DHF patients. Systematic Review is the research method used in this study, where the author collect evidence in accordance with predetermined criteria to answer questions that are the focus of the study. Based on 11 literatures used as data in this study, 7 literatures stated that hematocrit was correlated with Dengue patient mortality, 5 literatures stated thrombocyte was correlated with mortality in Dengue patients, 2 literatures stated hematocrit was not correlated with mortality in Dengue patients, 4 literatures stated thrombocyte was not correlated with mortality in Dengue patients, and 2 literatures stated nutritional status was correlated with mortality in Dengue patients. Hematocrit, Thrombocyte and nutritional status are correlated with DHF patient mortality.